(untitled) (Research, Society and Development, 2023)
Introduction: "Ranula" is the term used to refer to mucoceles that occur on the floor of the mouth. They are benign lesions that occur due to the phenomenon of extravasation of saliva into the surrounding tissue. Among the most common etiologies are traumas in the region of the sublingual gland or obstruction of the duct of this gland. Clinically, the ranula appears as a swelling with a bluish or translucent color, resembling the abdomen of a frog, which gave rise to its name. Objective: The objective of this work is to report the case of a male patient, aged 35 years, normossystemic, who attended the Oral Diagnosis Clinic of Faculdade Paulo Picanço, complaining of swelling in the sublingual region, caused by difficulty in feeding and movement of the tongue. To confirm the diagnosis, a histopathological examination was performed, which confirmed the hypothesis of ranula. Therefore, surgical excision of the lesion was performed. The patient was followed up for a period of 1 year and showed no signs of recurrence. Final considerations: Surgical excision of the lesion is considered a conservative approach compared to marsupialization and excision of the sublingual gland, but it has high success rates. After the procedure, it is essential that the patient is monitored to ensure the effectiveness of the treatment and provide a better prognosis.